The Current Status of the Security Council's Role in International Peace and Security - Dr. Pankaj Tyagi; Dr. Reema Agrawal (International Journal of Engineering and Management Research, 2020)
The maintenance of international peace and security is the UN's fundamental goal, as stated in Article 1 of its charter. To that end, the organization must "take effective collective measures for the prevention and removal of threats to the peace, the suppression of acts of aggression or other breaches of the peace, and the peaceful adjustment or settlement of international disputes or situations that may lead to a breach of the peace." Over the years, the UN has taken on this massive role with different degrees of effectiveness. In the nuclear age, however, international security without an organization like the United Nations is unthinkable. Since 1945, 2,247 UN peacekeepers have died in the service of international peace and security, as of 31 March 2006. In 1988, the Nobel Peace Prize was awarded to the United Nations peacekeeping forces in appreciation of their important contribution to world peace.